Vipassanā- Ekāyano ayaṁ, maggo sattānaṁ visuddhiyā (Bodhi Path, 2024)
In Buddhism the universe and the life therein are governed by the natural law of Cause and Conditions and conditionally originated phenomena, creating a self –sustaining mechanism. “The principle of Dependent Origination.” In this paper, we present the content of Mahāsatipaṭṭhāna Sutta in context of principle of Dependent Origination and the way how to meditate as defined in this sutta. The utmost efforts are being made to justify the title as per the teachings of the Great Buddha. This paper covers under the subtitles- The Way of meditation leading for liberation, a brief of Mahāsatipaṭṭhāna Sutta and ultimately Conclusion, Bibliography.
Keywords: Mahāsatipaṭṭhāna; Kāyānupassanā; Vedanānupassanā; Cittānupassanā; Dhammānupassanā; Ānāpānapabbaṃ; Iriyāpathapabbaṃ; Nibbāna; satabojjhianga; pancanivrana; salayana; pancasankhda